(untitled) - Deshmukh, Yeshvant V. (Boca Raton, 2005)
Industry relies on heating for a wide variety of processes involving a broad range of materials. Each process and material requires heating methods suitable to its properties and the desired outcome. Despite this, the literature lacks a general reference on design techniques for heating, especially for small- and medium-sized applications. Industrial Heating: Principles, Techniques, Materials, Applications, and Design fills this gap, presenting design information for both traditional and modern heating processes and auxiliary techniques.
Keywords: Heating,Furnaces